A prospective cohort study of newborns born to mothers with serum Toxoplasma gondii immunoglobulin M positivity during pregnancy. Issue 4 (April 2022) - Hijikata, Midori; Morioka, Ichiro; Okahashi, Aya; Nagano, Nobuhiko; Kawakami, Kaori; Komatsu, Atsushi; Kawana, Kei; Ohyama, Shohei; Fujioka, Kazumichi; Tanimura, Kenji; Deguchi, Masashi; Sasai, Miwa; et al.
Abstract: Introduction: The aims were to investigate the clinical characteristics of Toxoplasma gondii (T. gondii) immunoglobulin (Ig) M-positive mothers and to clarify the incidences of serum T. gondii IgM or blood T. gondii DNA positivity in newborns born to the mothers and the actual congenital T. gondii infection. Methods: Mothers with T. gondii IgM positivity and newborns born to the mothers from 2013 to 2020 were prospectively investigated. Serum T. gondii IgG and IgM were measured by enzyme-linked immunosorbent assay. Blood T. gondii DNA was detected by semi-nested polymerase chain reaction. Congenital T. gondii infection was diagnosed based on clinical characteristic manifestations with serum T. gondii IgG positivity at any age or T. gondii IgG positivity after 12 months of age. Results: Among 71 T. gondii IgM-positive mothers, including one with triplets, 41% had low T. gondii IgG avidity index and 73% received maternal therapy. Among 73 newborns who were examined for serum T. gondii IgG and IgM at birth, none had clinical manifestations, and one (1.4%) had T. gondii IgM positivity. Among 32 newborns who were examined for blood T. gondii DNA at birth, two (6.3%) were positive. All patients with serum T. gondii IgM or blood T. gondii DNA positivity showed T. gondii IgG negativity within 12 months of age. Conclusions: A few newborns born to T. gondii IgM-positive mothers were suspected of having congenital T. gondii infection based on serum T. gondii IgM or blood T. gondii DNA testing at birth. However, none developed congenital T. gondii infection.